Density functional theory insights into ternary layered boride MoAlB. (15th June 2017) - Bai, Yuelei; Qi, Xinxin; Duff, Andrew; Li, Ning; Kong, Fanyu; He, Xiaodong; Wang, Rongguo; Lee, Willam Edward
Abstract: Density functional theory is used to provide theoretical insights into the ternary nanolaminated and layered transition metal boride (MAB phase) of MoAlB, with calculations of crystal structure, electronic structure, lattice dynamics and elastic properties, including a corresponding hypothetical MAX phase compound Mo2 AlC for comparison. The calculated atomic configuration matches well with experiment. The metal-like electronic structure contributes to the physical origin of the high electrical conductivity of MoAlB. Strong covalent bonding is present between the B atoms, as well as between the Mo and B atoms, and significantly the much weaker AlAl bonds are consistent with the high fracture toughness and damage tolerance seen in MoAlB. With increasing pressure, the shrinkage is highest along the b axis, and lowest along the c axis. From the calculated second-order elastic constants, the bulk moduli B, shear moduli G, Young's moduli E and Poisson ratio μ are 207 GPa, 137 GPa, 336 GPa and 0.23, respectively. The G / B ratio of 0.66—similar in magnitude to values in MAX phases –demonstrate similarities in properties between MAB and MAX phases. Lattice dynamics are examined in detail, with 9 Raman-active modes and 6 infrared-active modes identified and analyzed in terms of their atomic motion and wavenumbers. Graphical abstract: Image